2011
DOI: 10.1590/s0104-14282011005000036
|View full text |Cite
|
Sign up to set email alerts
|

Poliolefinas reforçadas com fibras vegetais curtas: sisal × curauá

Abstract: Resumo: É crescente o interesse nos compósitos poliméricos reforçados com fibras vegetais curtas em substituição às fibras de vidro, pois as fibras naturais provêm de fontes renováveis, não são abrasivas aos equipamentos de processamento, são biodegradáveis, e possuem baixa densidade comparada às fibras de vidro. Elas apresentam início de degradação em torno de 200 °C, sendo adequadas para reforçar poliolefinas que são processadas até essa temperatura ou termofíxos. Várias fibras vegetais vêm sendo usadas como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
0
17
0
11
Order By: Relevance
“…SPINACÉ et al [2] and ETAATI et al [11] also observed this behavior, once natural fibers are usually less resistant than glass fibers. Although the composites with natural fibers have lower mechanical properties when compared to glass fiber composite, the difference is relatively small, for instance the wood fiber composite with coupling agent (PP+(CA)+WF) showed Flexural modulus of 69.56 MPa versus 75.78 MPa for the reference composite (PP+GFPP).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…SPINACÉ et al [2] and ETAATI et al [11] also observed this behavior, once natural fibers are usually less resistant than glass fibers. Although the composites with natural fibers have lower mechanical properties when compared to glass fiber composite, the difference is relatively small, for instance the wood fiber composite with coupling agent (PP+(CA)+WF) showed Flexural modulus of 69.56 MPa versus 75.78 MPa for the reference composite (PP+GFPP).…”
Section: Resultsmentioning
confidence: 81%
“…In general the elastic modulus of all the composites with natural fibers showed lower mechanical properties when compared to reference material (PP+GFPP), Figure 1-b. The transfer of the applied stress can be hampered by the presence of discontinuous short fibers dispersed in the polymeric matrix, thus reducing tension supported by the composite [2,[12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of fiber have been widely investigated and used as reinforcement in polymer matrices such as sponge gourd fiber [4] , sisal [5] , curauá [5] , sugar beet pulp [6] and sugarcane bagasse fiber [7] . Acacia bark residues was used as reinforcing filler in polypropylene composite can produce higher impact properties and higher degradation temperature [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Todos esses fatores são hoje muito importantes para a manutenção das empresas em uma situação economicamente viável no ambiente de hipercompetitividade associado à globalização da economia e flexibilização dos mercados regionais [8] . As pesquisas sobre fibras naturais em matrizes poliméricas de compósitos desenvolvidas recentemente incluem, por exemplo: o uso de fibra de coco em biocompósitos [9] e em Polipropileno [10] , piaçava em poliéster [11] , fibras em compósitos no contexto amazônico [12] , curauá em Poliamida [13] , sisal e curauá em poliolefinas [14] , sisal em biocompósitos [15,16] , em borracha nitrílica [17] e em Polipropileno e Polietileno [7], dentre outras.…”
Section: Introductionunclassified